MANUAL DE BUENAS PRÁCTICAS DE LABORATORIO - Cervantes Peralta, Marieta; Gutiérrez Rico, Lourdes Maribel; Reynoso Zárate, Auristela Florencia; Canihua Rojas, Jorge; López Galán, Edinson Eduardo; Munarriz Aedo, Jesús Sixto; Flores de Garay, Irene; Sales Dávila, Beatriz; Guerrero Lázaro, Juan Miguel (Instituto Nacional de Innovación Agraria, 2021)
190 páginas